Meningkatkan Aktivitas Dan Hasil Belajar Menggunakan Kombinasi Model Pbl, Tai Dan Make A Match Pada Siswa Kelas 5 SDN Kuin Utara 7 Banjarmasin - Dina Evi Irawati; Khairil Khairil Anwar (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
The issue in this study is the low movement and learning results of understudies. Endeavors to further develop understudy learning exercises and results by utilizing a blend of Issue Based Learning, Group Helped Individualization, and Make a Match models. The motivation behind this study is to portray the exercises of educators, understudies, and to investigate understudy learning results. This examination utilizes a subjective methodology with the sort of Study hall Activity Exploration (Vehicle). The examination was led at four gatherings, while the subject of this exploration was understudies in grade 5 even semester at SDN Kuin Utara 7 Banjarmasin in the scholarly year 2023/2024 with a sum of 17 understudies. The sorts of information in this study are subjective and quantitative information. The outcomes showed that the mix of Issue Based Learning (PBL) models, Group Helped Individualization (TAI), Make a Macth in the second gathering of the fourth cycle showed that educator action scored 35 rates (95%) with the "Excellent" measures, understudy exercises scored 15 rates (88%) with the rules "Exceptionally Dynamic and Dynamic" and accomplishing traditional fulfillment understudy learning results 17 rates (100 percent) with "Finished" standards. In light of these discoveries it very well may be presumed that this blend of models can increment understudy learning exercises and results and is recommended as an elective reference in utilizing the model.